Conventional Therapeutic Plasma Exchange Versus Low Volume Plasma Exchange in Chronic Pathologies: Potential Benefit in Alzheimer's Disease. (October 2022) - Escolar, Ginés; Páez, Antonio; Cid, Joan
Conventional therapeutic plasma exchange (TPE) is aimed at removing pathological agents from circulation using a medical device which separates out plasma from other components of blood. Usually, 1.0 to 1.5 plasma volumes are removed and replaced with a replacement solution. There is strong clinical evidence for the effectiveness of TPE in a wide spectrum of diseases, such as thrombotic thrombocytopenic purpura, severe acute inflammatory demyelinating polyneuropathy, and Guillain-Barré syndrome, among others. However, therapeutic approaches using lower plasma exchange volumes (LVPE) suggest some degree of effectiveness in a number of pathological conditions, although generally with low level of clinical evidence: hematology disorders (autoimmune hemolytic anemia), neuroimmunological diseases (Guillain-Barré syndrome, neuromyelitis optica, myasthenia gravis, multiple sclerosis), pulmonary disorders, liver failure, dermatology (pemphigus) and metabolic diseases (porphyria, cholesterol). Further or newer studies are needed to confirm LVPE as an alternative to TPE for such groups of pathologies. While plasma volume removed for TPE ranges 3-4.5 L per procedure, for LVPE ranges from 350 mL to 2 L (frequency and duration vary depending on the pathology treated). In the case of Alzheimer's disease (AD), the AMBAR trial recently investigated a combined sequence of intensive TPE with human albumin replacement followed by a maintenance phase LVPE (650-880 mL of plasma removed, similar to a plasma donation). The treatment slowed the decline or stabilized the disease symptoms. The AMBAR approach could justify investigating the use of LVPE in chronic conditions where plasma exchange strategies have proven successful.